Social technologies under conditions of informatization (sociocultural analysis) - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article focuses on the characteristics of development of social technologies under modern sociocultural conditions.